2016
DOI: 10.1371/journal.pone.0160850
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Social Cognition in Amyotrophic Lateral Sclerosis: A Population Based Study

Abstract: Background: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neurodegenerative disease. Executive dysfunction is common in patients with ALS, with up to 50% of patients performing within an impaired range. There is evidence that social cognitive deficits associated with ALS are a function of deficits in executive function. The ‘Reading the Mind in the Eyes’ Test is a recognized test of social cognitive function, although the reliability of this instrument remains to be established. Methodology: Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…Some evidence supports a stronger association between executive functions and “fluid intelligence,” both involving mainly dorsolateral prefrontal networks (Roca et al, 2012), in contrast to ToM processes, hypothesized to be probably more dependent from medial prefrontal networks, especially with regard to the affective subcomponent (Shamay-Tsoory et al, 2005, 2006; Xi et al, 2011; Bertoux et al, 2016). However, more recently, Burke et al (2016b) demonstrated a significant impairment of ET, as a measure of affective social cognition, in ALS patients with executive dysfunctions compared to healthy subjects. Probably, these inconsistent results may be due by the fact that the anatomical and biological bases of the ToM performances are still debated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence supports a stronger association between executive functions and “fluid intelligence,” both involving mainly dorsolateral prefrontal networks (Roca et al, 2012), in contrast to ToM processes, hypothesized to be probably more dependent from medial prefrontal networks, especially with regard to the affective subcomponent (Shamay-Tsoory et al, 2005, 2006; Xi et al, 2011; Bertoux et al, 2016). However, more recently, Burke et al (2016b) demonstrated a significant impairment of ET, as a measure of affective social cognition, in ALS patients with executive dysfunctions compared to healthy subjects. Probably, these inconsistent results may be due by the fact that the anatomical and biological bases of the ToM performances are still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of social cognition has also been described in several cohorts of patients in heterogeneous stages of ALS (Girardi et al, 2011; Van der Hulst et al, 2015; Burke et al, 2016a,b). Moreover, abnormalities of both cognitive and affective ToM, related to social behavior dysfunctions, such as loss of empathy and apathy (Gregory et al, 2002; Girardi et al, 2011), have been recently confirmed as a prominent feature of behavioral profile in advanced ALS (Van der Hulst et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patients also have impaired emotional facial expression recognition, impaired emotional responses, impaired excitability in response to emotional stimuli, and impaired judgment of emotional valence ( 4 , 5 ). Affective and cognitive Theory of Mind (ToM) is also affected by the disease ( 6 , 7 ), this finding having been shown to be discrepant when comparing within ALS patients, stratified by bulbar and spinal onset in some studies ( 8 , 9 ), but not in others ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Christidi et al reviews the evidence for memory deficits in MND with a painstaking analysis of the available clinical(52), radiological (1) and post mortem literature(53). Professor Mioshi's group eloquently reviews the impact of cognitive and behavioral deficits in ALS on patients and caregivers drawing attention to an important aspect of ALS care which is relatively understudied(54,55).The novelty of their analysis lies in the identification of viable non-pharmaceutical strategies to improve patient and caregiver well-being (Caga et al). Grollemund et al perform an in-depth analysis of the ever expanding literature of machine-learning in MND, and discuss the advantages and drawbacks of specific mathematical models.…”
mentioning
confidence: 99%